2011
DOI: 10.1016/j.brainres.2010.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal separation, early handling, and gonadal sex on regional metabolic capacity of the preweanling rat brain

Abstract: This is the first study to assess the effects of mother-infant separation on regional metabolic capacity in the preweanling rat brain. Mother-infant separation is generally known to be stressful for rat pups. Holtzman adolescent rats show a depressive-like behavioral phenotype after maternal separation during the preweanling period. However, information is lacking on the effects of maternal separation on the brains of rat pups. We addressed this issue by mapping the brains of preweanling Holtzman rat pups usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
3
22
0
2
Order By: Relevance
“…Our results are coincident with current literature regarding maternal separation before weaning (Sanchez et al, ; Meagher et al, ; Spivey et al, ; Bonab et al, ; Wall et al, ; Vetulani ; Melo, ; Segura et al, ; Sieben et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are coincident with current literature regarding maternal separation before weaning (Sanchez et al, ; Meagher et al, ; Spivey et al, ; Bonab et al, ; Wall et al, ; Vetulani ; Melo, ; Segura et al, ; Sieben et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Once again, all these authors find changes mainly in hippocampus and amygdala, although in this case, the thalamus and medial prefrontal cortex (PFC) is also altered. Some authors have found changes in the metabolism of PFC (Spivey et al, ) even in short‐term separations (handling), despite the so‐called “positive effect” (Melo, ); and in some cases, there are changes that depend on gender (León‐Rodríguez and Dueñas, ). As can be seen, the wide variety of protocols makes difficult to have a big panorama of the effects of social isolation, both before‐ and after‐weaning, and in some cases, contradictory recalls of the observed changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduced stress response was again associated with reduced CRH expression in the hypothalamus and increased GR in the hippocampus (Avishai-Eliner, Eghbal-Ahmadi, Tabachnik, Brunson, & Baram, 2001;Meaney et al, 1996), suggesting a similar pattern of alteration in the brain due to different manipulations that all seem to result in resilience. Further, early handling also led to improved cognitive function and reduced risk for depressive-like behavior (Dinces, Romeo, McEwen, & Tang, 2014;Meaney et al, 1991;Reeb-Sutherland & Tang, 2012;Spivey, Padilla, Shumake, & Gonzalez-Lima, 2011;Tang, 2001), suggesting that the extra stimulation early in life leads to a more resilient phenotype that is based on alterations in HPA axis functioning.…”
Section: Models Of Els Suggest That the Dam May Have A Huge Impact Onmentioning
confidence: 99%